Engaging nutrition stakeholders in Poyentanga: A case study on local-level multisector coordination - Billings, Lucy; Wullingdool, Emmanuel (International Food Policy Research Institute, 2019)
Multisectoral coordination and action are recognized as necessary conditions to effec-tively address the multiple drivers of malnutrition. There has been a strong effort in the past decade to establish multisector coordination at the national level among member states of the Scaling Up Nutrition Movement. However, the practice of subnational and commu-nity-level nutrition coordination is still emerging, and literature on the factors related to the formation and success of such coordination bodies is limited (for example, Harris et al. 2017). Understanding contextual factors is particularly important for supporting local-level ena-bling environments, where traditional customs may hold influence over political and social structures. A multisector nutrition committee was formed in Poyentanga, a subdistrict of Wa West District in the impoverished Upper West region of Ghana, where acute child malnutrition is driven by seasonal food insecurity. The committee was launched in November 2018 as a plat-form to coordinate local stakeholders to address the challenges of persistent malnutrition in the communities of Poyentanga. This case study examines the enabling environment for local-level engagement and action on nutrition to understand the context and the key factors that led to the formation of the Poyentanga nutrition committee. The basic policy framework and institutional structures were already in place for multi-sector coordination on nutrition before the committee was established. The National Nutrition Policy specifies the formation of a multisectoral coordination mechanism for nutrition services and programmes at national and subnational levels, and responsibility for resource allocation for the delivery of necessary services sits with the District Assemblies. Yet a strong focus on the treatment of acute malnutrition in Wa West District had left the administration of curative nu-trition services largely to the health sector, with little attention given to preventative ap-proaches or engagement from other sectors. Once attention was drawn to the prevalence and consequences of malnutrition, stakeholders from across sectors demonstrated high commit-ment to addressing the problem.